2017
DOI: 10.1177/0003702816689099
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy for the Rapid Characterization of Lead-Free Gunshot Residues

Abstract: This study investigated the use of laser-induced breakdown spectroscopy (LIBS) and scanning electron microscopy energy dispersive X-ray spectroscopy (SEM-EDX) as means of characterizing gunshot residue (GSR) originating from commercially available lead-free rounds. Data from two experiments are presented in this work. One experiment focused on identifying prominent analytical markers present in lead-free GSR by LIBS while the other applied SEM-EDX to determine the degree of evidence preservation after LIBS ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The method is relatively simple and can be considered almost nondestructive due to the small sample size required. In recent studies, LIBS was found to be very effective for glass and GSR analyses. ,, A nonspectroscopic technique which provides elemental composition is LA-ICPMS, which was shown by Almirall and Trejos to be propitious for the analysis of various materials …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method is relatively simple and can be considered almost nondestructive due to the small sample size required. In recent studies, LIBS was found to be very effective for glass and GSR analyses. ,, A nonspectroscopic technique which provides elemental composition is LA-ICPMS, which was shown by Almirall and Trejos to be propitious for the analysis of various materials …”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, while LIBS was successful for pattern visualization, it should not be used as a replacement for SEM-EDX analysis. Fambro et al published two studies which investigated the potential for LIBS to be used for the analysis of GSR stemming from ammunition having lead-free composition. , They utilized LIBS in conjunction with SEM-EDX for both of these studies and emphasized the potential for LIBS to be used as a prescreening method before analysis using SEM-EDX. An example of the types of SEM-EDX maps used to correlate and compare with LIBS data in their 2017 study can be seen in Figure .…”
Section: Gunshot Residuementioning
confidence: 99%
See 1 more Smart Citation
“…The portable LIBS instrument was found to have over 90% correct classification 11 . Additional studies have further demonstrated the potential of LIBS to simultaneously provide both multielemental and spatial information around bullet orifices on large surface areas using different ablation patterns 22–23,29–31 . The results of these studies demonstrate the promise and versatility of a technique such as LIBS to strengthen the value of GSR evidence 1–2,11,32 …”
Section: Introductionmentioning
confidence: 82%
“…Previous publications have reported a list of typically monitored constituents for both conventional and lead‐free ammunition, as well as minor compounds (Abrego et al, 2014; Benito et al, 2015; Dalby et al, 2010; Fambro et al, 2016, 2017; López‐López et al, 2012; Martiny et al, 2008; Menking‐Hoggatt et al, 2021; Romanò et al, 2020). Research works like these are extremely valuable when making decisions about not only which compounds should be monitored, but also which type of analytical strategy is suitable for a given purpose.…”
Section: Heavy Metal‐free Ammunition Characterization: Alternative Me...mentioning
confidence: 99%